Nurturing the literate mind through group interaction among literary thinkers - Tina Abdullah; Zaidah Zainal; Abdul Halim Abdul Raof (Penerbit Universiti Kebangsaan Malaysia, 2021)
Conventional classroom discourse structure that nurtures literacy through the scientific way of thinking is argued to limit personal engagement and exploration of alternative thinking processes among literary thinkers. In nurturing literacy for the literate mind, this study investigated how the literary way of thinking through group interaction can become a powerful alternative avenue to complement the established scientific way of thinking. Based on the Reader Response and Envisionment Building theories, participants were given the freedom to wander and become personally involved in group interactions advancing thinking about meaning through exploring horizons of possibilities. Through peer-led group discussions, this case study examined a group of 31 undergraduate learners who discussed a short story as part of a literature course. The overall findings show that when given the freedom to explore horizons of possibilities through group interactions, the participants demonstrated personal engagement and the ability to explore different thinking processes. Among the common themes observed were that participants shared personal recalling of facts or literary devices, contemplated personal interpretations of meaning, discussed the personal evaluation of the text, expressed doubts or misunderstandings, made personal connections or extended the imaginary world. It may thus be concluded that to nurture the literate mind, the literary way of thinking should complement the scientific way of thinking to promote different thinking processes and personal engagement. Opportunities to explore horizons of possibilities through group interactions support literacy in literature classrooms.